DETERMINAN FAKTOR YANG MEMPENGARUHI KEHAMILAN REMAJA DI KAMPUNG NAFRI KOTA JAYAPURA TAHUN 2021 - Rerey, Heni Voni; Wahyuni, Sri; Tjoe, Paskahlia (NHM PRESS, 2022)
Adolescent pregnancy is a pregnancy that applies to women aged 11-19 years. The factors that influence teenage pregnancy include factors from within the individual, age at marriage, age at first sexual intercourse, educational status, knowledge of reproductive health, risky sexual behavior, substance abuse, and use of contraception. The purpose of this study was to determine the determinants of factors that affect teenage pregnancy in Nafri Village, Jayapura City. Methods: Qualitative descriptive research with a case study approach and in-depth interview methods. Data analysis using content analysis. Results: Determinant Factors of Teenage Pregnancy in Nafri Village are as follows because of the behavior of wanting to experiment, because the boyfriend wants to ask for proof of love, getting carried away, teenagers lack knowledge about early pregnancy, parents have a role in advising not to get caught up in promiscuity, and the role of accessing free porn videos.